Reducing income-related inequities in colorectal cancer screening: lessons learned from a retrospective analysis of organised programme and non-programme screening delivery in Winnipeg, Manitoba - Decker, Kathleen M (BMJ Open, 2016)
OBJECTIVE: We examined organised colorectal cancer (CRC) screening programme and non-programme faecal occult blood test (FOBT) use from 2008 to 2012 for individuals living in Winnipeg, Manitoba, by area-level income. SETTING: Winnipeg, Manitoba, a region with universal healthcare and an organised CRC screening programme. PARTICIPANTS: Individuals who had a non-programme FOBT were identified from the Provincial Medical Claims database. Individuals who had a programme FOBT were identified from the provincial screening registry. Census data were used to determine average household income based on area of residence. STATISTICAL ANALYSIS: Trends in age-standardised FOBT rates were examined using Joinpoint Regression. Logistic regression was performed to explore the association between programme and non-programme FOBT use and income quintile. RESULTS: FOBT use (non-programme and programme) increased from 32.2% in 2008 to 41.6% in 2012. Individuals living in the highest income areas (Q5) were more likely to have a non-programme FOBT compared with those living in other areas. Individuals living in areas with the lowest average income level (Q1) were less likely to have had programme FOBT than those living in areas with the highest average income level (OR 0.80, 95% CI 0.77 to 0.82). There was no difference in programme FOBT use for individuals living in areas with the second lowest income level (Q2) compared with those living in areas with the highest. Individuals living in areas with a moderate-income level (Q3 and Q4) were more likely to have had a programme FOBT compared with those living in an area with the highest income level (OR 1.12, 95% CI 1.09 to 1.15 for Q3 and OR 1.10, 95% CI 1.07 to 1.13 for Q4). CONCLUSIONS: Inequities by income observed for non-programme FOBTs were largely eliminated when programme FOBTs were examined. Targeted interventions within organised screening programmes in very low-income areas are needed.